Impact voltage deviation on the technological characteristics of crushers - Savchenko, V.; Sinyavsky, A. (Національний університет "Львівська політехніка", 2013)
The results of research on the influence of voltage deviation on the technological characteristics and energy losses in electric drive of the crusher are presented. Dependence of the productivity, of specific consumption of energy and grinding module on the voltage are established.
Keywords: crusher; electric drive; voltage deviation; productivity; specific consumption of energy; power loss; the grinding module